Edutainment Si Galang (Gizi Seimbang dan Gigi Cemerlang) sebagai Upaya Zero New Tuberculosis (Tbc) pada Anak - Sri Redjeki Indianai; Sofiatun Sofiatun; Winda Kusumawardani; Berliana Devianti Putri; Haly Nur Cahyawan (Universitas Baiturrahim, 2026)
Tuberculosis (TB) remains a global health problem with a very high incidence rate. SITB data in 2014 showed that the coverage of TB cases in children was 67%, with a prevalence of 91.2% in East Java and 80.5% in Ponorogo Regency. An interview at SDN 2 Suren, Mlarak District, Ponorogo Regency, revealed that there had been a student infected with mycobacterium tuberculosis. The symptoms that appear in children with TB are often overlooked and tend to resemble other common illnesses, while risk factors such as poor nutritional status and oral health problems further worsen the child’s immune condition. Limited access to information in remote areas has led to suboptimal education about TB and the importance of child health. The community service team carried out an interactive educational program called Edutainment SI GALANG (Balanced Nutrition and Bright Teeth). The activity involved 60 participants, grades I to VI. Pre-test results showed 50% of participants had sufficient knowledge, and 28.3% had insufficient knowledge. This situation illustrates that before the education, most participants did not understand the causes, symptoms, or prevention of TB. Furthermore, post-test results showed a significant increase, with 85% of participants having good knowledge, 11.7% having sufficient knowledge, and only 3.3% having insufficient knowledge. This improvement indicates that children who initially had difficulty answering questions about the causes and symptoms of TB were able to correctly explain how TB is transmitted, how to prevent transmission, and the importance of maintaining personal and environmental hygiene after the activity. This demonstrates that the edutainment-based educational activity successfully increased participants' absorption of the material presented.